Pengaruh Model Project Based Learning (PjBL) Berbasis Produk Digital terhadap Hasil Belajar dan Keterampilan Digital Siswa Fase E SMA Negeri 7 Padang: The Influence of the Digital Product-Based Project Based Learning (PjBL) Model on Learning Outcomes and Digital Skills of Phase E Students of SMA Negeri 7 Padang - Ria Angrianie (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Implementation of the Independent Curriculum has resulted in a reduction in the study load and learning hours, especially face-to-face learning hours in the classroom. In addition to reducing learning hours, there is also a reduction in teaching materials that burden students. The Independent Curriculum emphasizes the development of competencies, character development, and student creativity. Digital literacy does not only include understanding the information received and making wise decisions based on that understanding. Digital skills refer to the ability to develop digital technology, hardware, software, applications, and communication tools effectively to solve problems, collaborate, and produce information. This study aims to determine the effect of the Project Learning (PjBL) model based on digital products on student learning outcomes and improving the digital skills of phase E students at SMA Negeri 7 Padang. The data collection technique in this study is a literature review, which takes from previous research and the implementation of the PjBL program. This study provides a literature review of the effect of PjBL in improving students' learning outcomes and digital skills and proposes an efficient way to develop digital products for students. This research will complement previous research related to digital product-based PjBL, suggest directions for future research, and improve the accuracy of future research results related to the topic of discussion.